Penegakan Hukum Terhadap Tindak Pidana Perundungan Melalui Dunia Maya (Cyberbullying) Di Polresta Cirebon - Ilyas, Raihan; Rahman, Nur; Dewi, Elya Kusuma (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2024)
The rapid development and progress of information and communication technology in the field of social media at all levels of Indonesian society, however, the development of social media also has negative impacts, one of which is the phenomenon of criminal behavior, such as oppression, bullying, harassment and insults online, which better known as the crime of Cyberbullying. This research aims to understand how law enforcement is implemented by the Cirebon Police in overcoming the phenomenon of cyberbullying. The research approach applied in this study involves 2 (two) different approaches, namely the empirical juridical approach and the normative juridical approach. Data collection techniques used in this research include observation, interviews and documentation. The results of this research show commitment to dealing with cybercrime. The existing legal framework, especially the Information and Electronic Transactions Law (UU ITE), is the basis for handling these cases. However, there are several challenges faced, such as the anonymity of the perpetrators, digital evidence being deleted and low public awareness, especially parents who do not supervise their children in using social media properly and correctly. what hinders this main goal is that it all depends on the victim who is dissatisfied with the mediation method. Victims sometimes want to continue the process to court because the victim wants the perpetrator to be punished as severely as possible.